Evaluation of the Dynamics of Microbiological Quality in Lightly Pickled Napa Cabbages During Manufacture. Issue 4 (16th April 2015) - Masuda, Kazuya; Yamamoto, Shiori; Kubota, Kunihiro; Kurazono, Hisao; Makino, Sou‐ichi; Kasuga, Fumiko; Igimi, Shizunobu; Asakura, Hiroshi
Abstract Following a large outbreak of Shiga toxin‐producing Escherichia coli (STEC) O157 infection in 2012, the prerequisite program for the production of pickles in Japan was revised to include disinfection with sodium hypochlorite (NaClO). Here, we examined the indicator bacterial counts, incidence of STEC and Salmonella spp. (by polymerase chain reaction [PCR] screening), and bacterial community composition (by 16S rRNA pyrosequencing analysis) from the intermediate products and the related facilities at a collaborative factory to evaluate the dynamics of microbial quality in lightly pickled vegetables during the manufacturing process following the revised program. Plate counts showed a significant reduction in coliform counts throughout processing, whereas the reduction in total viable counts was relatively less than that of coliforms. No STEC and Salmonella spp. were recovered from any of the samples. 16S rRNA pyrosequencing analysis revealed the process‐by‐process alteration of bacterial community composition in which the yields of Pseudomonas spp. were drastically affected by soaking in high concentration of NaCl. In summary, we demonstrate that the revised prerequisite program is indeed functional to reduce the microbial risks. Practical Applications Fresh or minimally processed produce are common vehicles of foodborne pathogens that have been responsible for several outbreaks worldwide. Through the use of indicator bacterial counts in combination with a metagenomic approach, we could trace the process‐by‐process dynamics of bacterial community composition. Information and relief provided to manufacturers/consumers could help improve public health and food safety.